Consistent predictors of microbial community composition across spatial scales in grasslands reveal low context‐dependency - Dajana Radujković; Sara Vicca; Margaretha van Rooyen; Peter Wilfahrt; Leslie Brown; Anke Jentsch; Kurt O. Reinhart; Charlotte Brown; Johan De Gruyter; Gerald Jurasinski; Diana Askarizadeh; Sandor Bartha; et al. (Molecular Ecology, 2023)
Environmental circumstances shaping soil microbial communities have been studied extensively. However, due to disparate study designs, it has been difficult to resolve whether a globally consistent set of predictors exists, or context‐dependency prevails. Here, we used a network of 18 grassland sites (11 of those containing regional plant productivity gradients) to examine (i) if similar abiotic or biotic factors predict both large‐scale (across sites) and regional‐scale (within sites) patterns in bacterial and fungal community composition, and (ii) if microbial community composition differs consistently at two levels of regional plant productivity (low vs. high). Our results revealed that bacteria were associated with particular soil properties (such as base saturation) and both bacteria and fungi were associated with plant community composition across sites and within the majority of sites. Moreover, a discernible microbial community signal emerged, clearly distinguishing high and low‐productivity soils across different grasslands independent of their location in the world. Hence, regional productivity differences may be typified by characteristic soil microbial communities across the grassland biome. These results could encourage future research aiming to predict the general effects of global changes on soil microbial community composition in grasslands and to discriminate fertile from infertile systems using generally applicable microbial indicators.